2021
DOI: 10.1177/0020881720981222
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Graduate Student Journals in the Publish-or-Perish Academy? Three Lessons from Three Editors-in-Chief

Abstract: To be prepared to face the “publish-or-perish” reality of contemporary academia, early career scholars must develop capacity and confidence. While the publication practices of International Relations have received increasing attention in the last 20 years, concern remains around the preparedness of graduate students to participate confidently and competently in the publication process. As three former Editors-in-Chief of a graduate student journal, we suggest that student-run journals can play an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…While prior research has discussed how online discussion forums can break down these barriers and contribute to active learning (King et al 2021 ), we were interested in developing a new method that would create space for deep engagement on fellow students’ work. This is not to deny the potential utility of discussion boards in some online circumstances—and indeed, some of the courses involved in this study incorporated discussion boards—but instead a call to recognize that participating in the peer review process can be a uniquely constructive experience for students (Arsenault et al 2021 ; Walker et al 2021 ). As Andrew and Michael began to prepare for their Fall 2020 semester courses, they considered how the rich exchange of ideas present in the academic peer review process might be replicated within the context of a course.…”
Section: Methodsmentioning
confidence: 99%
“…While prior research has discussed how online discussion forums can break down these barriers and contribute to active learning (King et al 2021 ), we were interested in developing a new method that would create space for deep engagement on fellow students’ work. This is not to deny the potential utility of discussion boards in some online circumstances—and indeed, some of the courses involved in this study incorporated discussion boards—but instead a call to recognize that participating in the peer review process can be a uniquely constructive experience for students (Arsenault et al 2021 ; Walker et al 2021 ). As Andrew and Michael began to prepare for their Fall 2020 semester courses, they considered how the rich exchange of ideas present in the academic peer review process might be replicated within the context of a course.…”
Section: Methodsmentioning
confidence: 99%
“…Much has been written on the multiple benefits for students if they publish in a journal (e.g., Cox & Kent, 2018; Rich, 2013), or participate in the editing and publishing process of a student‐oriented journal (e.g., Weiner & Watkinson, 2014). Some articles also detailed the workflow of particular student‐oriented journals (e.g., Barrios & Weber, 2006), and provided advice on how students can participate in these journals (e.g., Arsenault et al, 2021). The idea for students to take the lead in academic publishing is not a novel one, although very little attempt has been made to formalize what exactly is required for a publication to be ‘student‐oriented’ or ‘student‐run’.…”
Section: The Student‐oriented Model Of Academic Publishingmentioning
confidence: 99%
“…396–402). Skills that have been repeatedly stated in the literature and are indeed acquired by student editors include communication, collaboration, and leadership skills (e.g., Arsenault et al, 2021; Cox & Kent, 2018; Garbati & Brockett, 2018). Other skills, such as recruitment and personnel management, financial budgeting, project management, and marketing and publicity, ‘are as useful for practice as a solicitor as they are within academia’, and are indeed prominent motivations and pedagogical functions of student‐oriented legal publications (MacPherson & Peterson, 2017).…”
Section: Benefits Of the Student‐oriented Model In Hong Kong Legal Ac...mentioning
confidence: 99%
“…Research is already integrated with learning. Graduate students had to be ensured that they could be potential authors and see the course papers as possible future scholarly articles [26]. A number of participants suggested that students should present their papers in international conferences and publish their research papers before graduation.…”
Section: Comments and Suggestions For The Program Improvementmentioning
confidence: 99%